Public opinion and technology: the impacts of big data in public opinion studies under the look of pragmatism - Romanini, Vinicius (2022)
In this article we investigate how the study of public opinion is influenced by public opinion polls as they work as a means of inquiring reality. With the growing movement of datification in the world, scientific and technological transformations emerge and impact the field of public opinion studies. Today, on the one hand, we have traditional opinion polls and, on the other, the researches made possible by the advent of Big Data. In addition to a collection of methodological protocols, each model encompasses a meaning of "public opinion", going back to the old epistemological clash between theory and methodology present in this field of study. We will describe the main differences between these two models and then, under the perspective of Peirce's pragmatism as a theory of meaning, to analyze the transition we are going through today.